Developing an Interdisciplinary Hypothetical Inquiry learning model to enhance students' higher-order thinking and computational thinking skills - Septiantoko, Riko; Saliman, Saliman; Sudrajat, Sudrajat; Hartati, Yumi; Azizah, Primanisa Inayati (Universitas Negeri Yogyakarta, 2025)
This study aims to develop an Interdisciplinary Hypothetical Inquiry (IHI) learning model that is (1) feasible and practical, and (2) determine the effectiveness of this model in improving undergraduate students' higher-order thinking skills (HOTS) and computational thinking skills (CTS) in solving social problems in social science (IPS) education study programs. This research uses a design and development research approach which includes six stages: (1) problem identification, (2) goal description, (3) product design and development, (4) product testing, (5) evaluation of test results, and (6) communication of results. The development of the IHI learning model was tested through (1) feasibility tests by expert lecturers in the field of education, evaluation experts, and social science experts; (2) practicality test through observation of learning implementation and responses from lecturers and student users; and (3) effectiveness test using a quasi-experimental method with a sample of undergraduate students in Social Sciences Education, Yogyakarta State University. The research instruments include expert lecturer review and assessment sheets, HOT and CT test questions, observation sheets on the implementation of the IHI model, and user response questionnaires. The research results show that the IHI learning model (1) is feasible based on the assessment of expert lecturers; (2) practical with an implementation score of 4.54 (very practical), a lecturer response score of 3.9 (very practical), and a student response score of 4.5 (very practical); and (3) potentially effective based on the higher N-Gain HOTS and CTS values in the experimental class (0.63 and 0.56) compared to the control class (0.59 and 0.15), as well as the t-test results with significance value 0.00 (p < 0.05). The student-centered IHI learning model encourages collaboration and democratic learning through the stages: 1) problem orientation, (2) hypothesis brainstorming, (3) hypothesis development, (4) investigation design, (5) investigation data collection, (6) interpretation of investigation data, (7) reporting and communication of results. This research concludes that the IHI learning model is feasible, practical, and effective for increasing HOTS and CTS for students in the social studies education study program.